Effect of prostaglandin analogs: Latanoprost, bimatoprost, and unoprostone on matrix metalloproteinases and their inhibitors in human trabecular meshwork endothelial cells. (May 2020) - Heo, Jae Young; Ooi, Yen Hoong; Rhee, Douglas J.
Abstract: Bimatoprost, latanoprost, and unoprostone are prostaglandin F2α analogs (PGAs) and are used to lower intraocular pressure. We investigated the free acid effects of these three prostaglandin analogs: bimatoprost, latanoprost, and unoprostone on human matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMP) in the trabecular meshwork (TM) cells. Immunoblot results show that all three PGAs generally increased MMPs-1, 9 and TIMPs-4. Additionally, bimatoprost and latanoprost both increased MMP-3 and TIMP-2, while unoprostone had an indeterminate effect on both. Zymography results show that all three PGAs except unoprostone increased intermediate MMP-1 activity while bimatoprost and latanoprost increased MMP-9 activity. Together, these data suggest that the balance between MMPs and TIMPs correlate to the relative intraocular pressure lowering effectiveness observed in clinical studies of these PGAs. Highlights: All three PGAs: Bimatoprost, latanoprost, and Unoprostone generally increased MMPs-1, 9 and TIMPs-4. Bimatoprost and latanoprost both increased MMP-3 and TIMP-2, while unoprostone had an indeterminate effect on both. All three PGAs increased intermediate MMP-1 activity. Bimatoprost and latanoprost increased MMP-9 activity. The balance between MMPs and TIMPs correlates to the relative intraocular pressure lowering effectiveness. The worse IOP lowering effect of unoprostone may be due to its inability to affect MMP activity in TM.